Gable Frame Structure Planning Using Lrfd Method in Pamekasan Factory Warehouse Project - Ahmad Ridwan; Nur Indah Mukhoyyaroh (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2021)
Currently, the use of steel as a building construction has been widely used as the main material for building structures. Steel frames come in a variety of profiles and sizes. The use of steel frames can be adjusted to the type of construction to be built. From the results of the planning of the WF steel roof structure on the factory warehouse construction project in Pamekasan, it was obtained planning data: Gording using Profile C 125x50x40x4,5. Trekstang uses 8 mm diameter, Wind ties use 10mm diameter steel, Rafter uses WF 350x350x19x19 profile, column uses WF 350x350x19x19 profile, 8 pieces A325 bolts with 22 mm diameter, Hoist Crane Beam uses IWF Bulit-Up beam with 600x1144x18x22 profile, Base Plate uses a size of 500x500x8mm with a column of 600x600.